2021
DOI: 10.3389/fpsyg.2020.596762
|View full text |Cite
|
Sign up to set email alerts
|

The Lineage Theory of the Regional Variation of Individualism/Collectivism in China

Abstract: China has undergone a rapid process of modernization since 1949. The modernization process has accelerated with the development of the market economy and rural-to-urban migration after the 1980s. Nevertheless, Chinese regions still exhibit substantial differences in terms of individualist/collectivist cultural orientations. The rice theory and the climato-economic theory have attempted to explain this variation by analyzing provincial-level data. Based on a quantitative analysis of more granular, county-level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 19 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…Influenced by Confucianism and collectivism, they sacrificed their interests to meet the demands of the entire family. 11 A study showed that older adults were less likely to receive spousal care when the quality of the relationship was low. 9 In our study, however, spousal caregivers still provided care in this situation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Influenced by Confucianism and collectivism, they sacrificed their interests to meet the demands of the entire family. 11 A study showed that older adults were less likely to receive spousal care when the quality of the relationship was low. 9 In our study, however, spousal caregivers still provided care in this situation.…”
Section: Discussionmentioning
confidence: 99%
“…10 When an individual's desires collide with the requirements of the family, the family comes first, mandating individual allegiance to the family. 11 Therefore, it is necessary to explore how spousal caregivers cope with this situation.…”
Section: Introductionmentioning
confidence: 99%
“…Despite being under significant risk and pressure, our results showed that many Chinese participants were inclined to give up. Considering the collectivist structure of Chinese culture [ 63 , 64 ] with a public emphasis on the community’s wellbeing [ 65 ], our research results indicate that even in highly collectivist cultures, people are inclined to give up and dismiss the potential risks that their behaviors can pose to others. Theoretically, this poses an interesting research area for the future.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Chinese population are generally deemed to have a cultural tradition of collectivism, whereby the Han culture places a higher importance on the interests and goals of the family and lineage above those of the individual (Gong et al, 2021). In the United States, several studies have indicated that American culture has become increasingly individualistic over time (see Ogihara, 2017).…”
Section: Heroismmentioning
confidence: 99%